A CORRELATION ANALYSIS OF STUDENTS’ LANGUAGE LEARNING STRATEGIES USE AND THEIR ACADEMIC PERFORMANCE - Dina Rachmawati (STKIP Siliwangi, 2013)
The way people learn a foreign language may be different from one person toanother. The success of students’ learning may be affected by the strategieswhich are employed by them. Therefore, attracted by the problem, this paper isaimed to investigate Language Learning Strategies (LLS) employed by thestudents and its relationship with their academic performance. StrategyInventory of Language Learning Strategies from Oxford (1990) was adopted asthe main theory of the study. The subjects of the research were 30 second yearstudents of English Department of UNTIRTA (Universitas Sultan AgengTirtayasa) Serang, Banten Province. To collect the data of students’ LLS,Questionnaire of Strategy Inventory of Language Learning, (Oxford, 1990) wasadopted. Moreover, students’ academic performance was measured from theirGrade Point of Average (GPA).The study finds that, there is relationshipbetween students’ language learning strategies use and their academicperformance. It is shown by the value of r, which is 0,776, while the criticalvalue with df of 28 is 0.32 It means that the correlation is marked andsignificant. Thus, it suggess that the more a student employs language learningstrategies the better her/his academic performance is. KEYWORDS: LLS (Language Learning Strategies), SILL (Strategy Inventory ofLanguage Learning)